The Effect Of Training And Competence On Employee Performance At Xyz Health Foundation - Irfan Fitriansyah, Moh.; Indiyati, Dian (International Journal of Science, Technology & Management, 2025)
Background: This study aims to find out an overview of employee training, competencies, and performance at the XYZ Health Foundation. In addition, this study aims to determine the influence of each variable that can affect Employee Performance at the XYZ Health Foundation, namely training and competence. Research sample The sample to be taken in this study includes male and female employees at the XYZ Health Foundation with a total of 106 employees using purposive sampling techniques. Method: The analysis method used is a quantitative method with descriptive and verifiable/causative analysis. The instrument test was carried out with a validity test consisting of convergent validity and discriminant validity. In addition, a reliability test was carried out using a composite reliability approach. Data analysis was carried out using the Partial Least Square – Structural Equation Modeling (PLS-SEM) approach which will be processed with the help of Smart PLS 4.0 software. Results and Conclusions:The results of the study show that training has a positive influence on employee performance and competence also has a significant effect on employee performance. Training and competency simultaneously have a significant effect on employee performance at the XYZ Health Foundation. Effective training is able to support competency development, which ultimately contributes to improving overall employee performance.